Rock Art research in Namibia: a Synopsis - Nankela, Alma Mekondjo (Africana Studia, 2020)
Namibia has one of the most outstanding, diverse and extensive rock art records in Southern Africa. The country’s Rock art database currently holds detailed records of both paintings and engravings found in various settings. However, some of these sites have been recorded and published, while others remained unrecorded and unpublished. This paper attempts to highlight the history of rock art research in Namibia over the last 50 years to date, the period where increased research activities has been observed in the region; by examining where rock art research has been focused, looking at the different site’s settings, distribution, content, traditions, ethno-archaeological analogues, style, chronology and the aspects of management and conservation of the rock art sites in Namibia. Furthermore, we will critically discuss some of the challenges of studying rock art in Namibia, current research trends and future research perspectives. Here, I present an overview of rock art research in Namibia where I examine where rock art research has been focused and finally critically discuss some of the challenges of studying rock art in Namibia, current research trends and future research perspectives. Key words: Rock Art, Research and Namibia.